Double stratified stagnation-point flow of Williamson nanomaterial with entropy generation through a porous medium. Issue 4 (6th July 2019) - Khan, Muhammad Ijaz; Kiyani, M.Z.; Hayat, Tasawar; Faisal Javed, Muhammad; Ahmad, I.
Abstract : Purpose: This paper aims to address double-stratified stagnation-point flow of Williamson nanomaterial with entropy generation. Flow through porous medium is discussed. Energy equation is modeled in existence of viscous dissipation, Brownian motion and thermophoresis. Furthermore, convective boundary conditions are considered. Total entropy rate is presented. Design/methodology/approach: The non-linear flow expressions are converted to ordinary ones by implementation of suitable transformations. The obtained ordinary system is tackled for series solutions via homotopy analysis method. Findings: Till date no one has considered the irreversibility analysis in stagnation-point flow of Williamson nanomaterial with double stratification, porous medium and convective conditions. The basic objective of present research is to investigate the convective stagnation point flow of Williamson liquid with entropy concept and porous medium. Originality/value: As per the authors' knowledge, no such work is yet present in the literature.